Wapl is an essential regulator of chromatin structure and chromosome segregation - Tedeschi, Antonio; Wutz, Gordana; Huet, Sébastien; Jaritz, Markus; Wünsche, Annelie; Schirghuber, Erika; Davidson, Iain Finley; Tang, Wen; Cisneros, David A.; Bhaskara, Venugopal; Nishiyama, Tomoko; Vaziri, Alipasha; et al. (Nature, 2013)
Depletion of the cohesin-associated protein Wapl in mice is shown to increase the residence time of cohesin on DNA, which leads to clustering of cohesin in axial structures, and causes chromatin condensation in interphase chromosomes; the findings suggest that cohesin could have an architectural role in interphase chromosome organization.